Discovery of silyl proline containing HCV NS5A inhibitors with pan-genotype activity: SAR development. Issue 5 (1st March 2016) - Nair, Anilkumar G.; Zeng, Qingbei; Selyutin, Oleg; Rosenblum, Stuart B.; Jiang, Yueheng; Yang, De-Yi; Keertikar, Kerry; Zhou, Guowei; Dwyer, Michael P.; Kim, Seong Heon; Shankar, Bandarpalle; Yu, Wensheng; et al.
Graphical abstract: HCV NS5A inhibitors have shown impressive in vitro potency profiles in HCV replicon assays thus making them attractive components for inclusion in an all oral fixed dose combination treatment regimen. Herein we describe the research efforts that led to the discovery of silyl proline containing HCV NS5A inhibitors such as7e and8a with pan-genotype activity profile and acceptable pharmacokinetic properties. Abstract: HCV NS5A inhibitors have shown impressive in vitro potency profiles in HCV replicon assays thus making them attractive components for inclusion in an all oral fixed dose combination treatment regimen. Herein we describe the research efforts that led to the discovery of silyl proline containing HCV NS5A inhibitors such as7e and8a with pan-genotype activity profile and acceptable pharmacokinetic properties.